Thinness among children aged 5- 17 years living in Nakivale refugee settlement, South Western Uganda: A Cross-sectional study - Namubiru, Teddy; Mbabazi, Nestor; Namirembe, Terry; Lugobe, Henry Mark; Musiime, Victor (Research square, 2022)
Background: Hunger and malnutrition are rampant among refugees and displaced populations, many of whom are infants and children. We sought to determine the prevalence and factors associated with thinness among children aged 5-17 years living in Nakivale refugee settlement, Isingiro district, southwestern Uganda. Methods: This was a cross sectional study that enrolled children aged 5 to 17 years. Data were collected on the participant socio-demographic, family, dietary, medical, hygiene and refugee status factors. The prevalence of thinness was determined by ascertaining the total number of children with thinness over the total number of children studied. Multivariable logistic regression model was used to determine the factors independently associated with thinness with p< 0.05 level of significance. Results: A total of 420 children aged 5- 17 years were enrolled into the study. The median age (IQR) was 8.6 (6.8- 11.8) and majority 248 (59.1%) were female. The prevalence of thinness was 5.5% (95% CI: 3.7%-8.1%). The factors independently associated with thinness were; living with a chronic disease (aOR 6.47, 95%CI; 1.63 - 24.64, p= 0.008), use of water from natural sources (aOR 3.32, 95%CI; 1.27 - 8.71, p= 0.015), and duration of stay in the settlement of less or equal to 10 years (aOR 3.19, 95%CI; 1.15 - 8.83, p= 0.025). Conclusion: Thinness among children 5- 17 years in Nakivale refugee settlement is common. Thinness was more likely among children who are living with a chronic disease, used water from natural sources and had had a shorter duration of stay in the settlement. Our findings suggest that children with chronic disease should receive extra food supplementation and have routine growth monitoring as part of their chronic care. The study reiterates a need to have clean and safe water supply and close nutrition assessment and monitoring, especially for newly registered refugee children.
Keywords: Malnutrition; Thinness; Children; Refugees; Uganda